1998
DOI: 10.1097/00005537-199809000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tonsillectomy for recurrent throat infection in adults

Abstract: Our results suggest that early tonsillectomy in patients with recurrent throat infection may result in improved patient satisfaction, better health, and improved utilization of medical resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 5 publications
9
38
0
1
Order By: Relevance
“…Superior results were obtained after TE [65], [66]. This conclusion is supported by the findings in retrospective [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80] and prospective [81], [82], [83], [84] studies proving the positive effect on the quality of life after TE which was questioned by Stafford [85]. However, the quality of the studies is not comparable to the aforementioned studies of Paradise.…”
Section: Discussionsupporting
confidence: 56%
“…Superior results were obtained after TE [65], [66]. This conclusion is supported by the findings in retrospective [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80] and prospective [81], [82], [83], [84] studies proving the positive effect on the quality of life after TE which was questioned by Stafford [85]. However, the quality of the studies is not comparable to the aforementioned studies of Paradise.…”
Section: Discussionsupporting
confidence: 56%
“…Patients with at least three episodes per year, despite adequate medical therapy, may be considered as candidates for TE, and surgical treatment is definitely recommended for patients with more than four or five episodes per year [1,2]. Adult patients often have fewer or less severe tonsillitis episodes, yet the dominance of other indices of chronic disease, such as poor general health, time loss from school or work, decreased life quality due to systemic effects or comorbid diseases, group A β-hemolytic streptococcus carriage state, and increased serum concentrations of antibodies, which have also been considered as appropriate indicators for TE [3-5]. Unfortunately, there is no consensus for these arbitrarily used criteria, hinting at a need for more precise indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Only one single RCT [486] was identified that could not confirm a benefit of TE in comparison to conservative therapy. This was in contradiction to an own study of the authors, a trial published by Laing and McKerrow [487] and a study of Mui et al [488]. In cases of PTA, needle aspiration and incisional drainage were recommended as primary measure, with a risk of recurrence of about 10%.…”
Section: Resultsmentioning
confidence: 79%
“…Since the disease itself is unclear, a recommendation regarding indication for TE could not be given. In contrast to adults, children experience a decreasing number of tonsillitis episodes with time [13], [180], [403], [409], [410], [436], [438], [447], [484], [486], [487], [490] (grade A), [478], [488], [491] (grade B).…”
Section: Resultsmentioning
confidence: 99%